African migration: exploring the role of development and states - Flahaux, M; de Haas, H (International Migration Institute, 2014)
Africa is often seen as a continent of mass migration and displacement caused by poverty, violent conflict and environmental stress. Yet such perceptions are based on stereotypes rather than theoretically informed empirical research. Drawing on the migration and visa databases from the Determinants of International Migration – DEMIG project and the Global Bilateral Migration Database (GBMD), this paper explores the evolution and drivers of migration within, towards and from Africa in the post-colonial period. Contradicting common ideas of Africa as a 'continent on the move’, the analysis shows that intra-African migration intensities have gone down. This may be related to state formation and the related imposition of barriers towards free movement in the wake of decolonisation as well as the concomitant rise of nationalism and inter-state tensions. While African migration remains overwhelmingly intra-continental, since the late 1980s there has been an acceleration and spatial diversification (beyond colonial patterns) of emigration out of Africa to Europe, North America, the Gulf and Asia. This diversification of African emigration seems partly driven by the introduction of visa and other immigration restrictions by European states. Contradicting conventional interpretations of African migration being essentially driven by poverty, violence and underdevelopment, increasing migration out of Africa seems rather to be driven by processes of development and social transformation which have increased Africans’ capabilities and aspirations to migrate, a trend which is likely to continue in the future.